Upaya promotif peningkatan kesadaran kesehatan reproduksi : metode penyuluhan pada komunitas yang terpapar gas buang karbon - Joko Marwoto; Lusia Hayati; Sri Nita; Rachmat Hidayat; Septi Purnamasari; Rara Inggarsih (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
The tendency to increase the number of motorized vehicles can result in decreased air quality. The increasing number of motorized vehicles on the streets of major cities with various brands and types will increase the consumption of fuel oil and cause the effects of air pollution, which is one of the serious impacts of disrupting male reproductive health. Promotive efforts with discussion and question and answer lecture techniques were carried out to communities with serious exposure to vehicle exhaust emissions, namely online motorcycle taxi drivers. As many as 30 online motorcycle taxi riders have received benefits and solutions to improve the degree of male reproductive health.